Parabiblica Coptica - Miroshnikov, Ivan (Mohr Siebeck, 2023)
Der vorliegende Band befasst sich mit den koptischen parabiblischen Texten – jenen Texten, die nicht zur Bibel gehören, sich aber in gewisser Weise in ihrer Umlaufbahn bewegen. Die Beiträge umfassen ein breites Spektrum an literarischen Gattungen, darunter apokryphe Apostelakten und die sogenannten »apostolischen Memoiren«, und Themen.InhaltsübersichtI. Editiones Christian H. Bull/Alexander Kocar: The Acts of Andrew and Paul (CANT 239): A New Edition with an Introduction, Translation, and Notes – Dylan M. Burns: More Greek Philosophers Among the Copts: The Notes of Some Philosophers (MONB.BE) and the »Wisdom from Outside« in Pseudo-Evodius of Rome's Homily on the Passion and Resurrection – Ivan Miroshnikov: The Preaching of Philip: A New Edition of the Sahidic Fragments with an Introduction, Translation, and Notes II. Studia Dan Batovici: The »Apostolic Fathers« in Coptic: Problems and Overview – Lilia Frangulian: 24, 72, 1000: Biblical Numbers in the Investitures of the Archangels Michael and Gabriel – Nils Arne Pedersen: Heresies and Apocrypha in the Thirty-Ninth Festal Letter of Athanasius of Alexandria – Eugenia B. Smagina: Onomastik und Rechtschreibung von Lehnwörtern in koptischen Texten, insbesondere in den Apokryphen – Vincent W. J. van Gerven Oei/Alexandros Tsakos: Apostolic Memoirs in Old Nubian The present volume focuses on the Coptic parabiblical texts – those texts that do not belong to the Bible, but, in a sense, move in its orbit – which include not only the Apocrypha, but also the works of the Apostolic Fathers. The contributions deal with a wide range of topics and literary genres, including apocryphal acts and the so-called apostolic memoires. The volume is divided into two sections; editiones , which contains editions of several important texts in Sahidic Coptic and studia , which comprise five articles on Coptic parabiblical literature. The literary works discussed in the volume are examined as part of Coptic literature, regardless of whether they were originally composed in Coptic or translated into Coptic from Greek. Moreover, some of the contributions deal with the reception of Coptic literature in Arabic and Old Nubian literary traditions.Survey of contentsI. Editiones Christian H. Bull/Alexander Kocar: The Acts of Andrew and Paul (CANT 239): A New Edition with an Introduction, Translation, and Notes – Dylan M. Burns: More Greek Philosophers Among the Copts: The Notes of Some Philosophers (MONB.BE) and the »Wisdom from Outside« in Pseudo-Evodius of Rome's Homily on the Passion and Resurrection – Ivan Miroshnikov: The Preaching of Philip: A New Edition of the Sahidic Fragments with an Introduction, Translation, and Notes II. Studia Dan Batovici: The »Apostolic Fathers« in Coptic: Problems and Overview – Lilia Frangulian: 24, 72, 1000: Biblical Numbers in the Investitures of the Archangels Michael and Gabriel – Nils Arne Pedersen: Heresies and Apocrypha in the Thirty-Ninth Festal Letter of Athanasius of Alexandria – Eugenia B. Smagina: Onomastik und Rechtschreibung von Lehnwörtern in koptischen Texten, insbesondere in den Apokryphen – Vincent W. J. van Gerven Oei/Alexandros Tsakos: Apostolic Memoirs in Old Nubian
10.1628/978-3-16-162224-3
Keywords: Aufsatzsammlung; Coptic literature; Parabiblica; Praxis der Freundschaft; Religionsgeschichtliche Schule; taxprogression; Ökumenisches Lernen; Littérature copte; Littérature copte - Histoire et critique; Apostolic Fathers; Apocrypha; Christian Egypt; Old Nubian; Editionen; Textausgaben; Kirchengeschichte; Neues Testament; apostolic fathers; apocrypha; Editionen; Textausgaben - Theologie; Array